Effect of modification on the formation of nonmetallic inclusions in KP-T wheel steel - Polishko, S. (Техническая механика, 2017)
This paper is concerned with the effect of the components of a multipurpose modifier on the formation of nonmetallic inclusions in KP-T wheel steel. The aim of this work is to study the effect of multipurpose modifiers on the morphology and arrangement of nonmetallic inclusions and on the stabilization and improvement of mechanical properties. It is found that doping the melt of this metal with multipurpose modifies increases the stability of its chemical composition, thus improving its mechanical properties. System thermodynamic studies are conducted into the possible effect of the components of special modifiers under their interaction with the melt. The key thermodynamic parameters of compounds that can be formed in the melt when doping it with special modifiers are determined. It is proved that multipurpose modification improves the morphology of nonmetallic inclusions, which also contributes to the improvement of mechanical properties. В данной статье рассмотрено влияние действия компонентов многофункционального модификатора на формирование неметаллических включений в колесной стали марки КП-Т. Целью данной работы было исследование влияния модификаторов многофункционального действия на морфологию и расположение неметаллических включений, а также на стабилизацию и повышение уровня механических характеристик. Установлено, что в данном металле при помощи ввода многофункциональных модификаторов в расплав стали повышается стабильность химического состава и, как следствие, уровень механических характеристик. Проведены системные термодинамические исследования по возможному влиянию компонентов специальных модификаторов при их взаимодействии с расплавом. Определены основные термодинамические параметры соединений, которые могут формироваться в расплаве сталей при введении специальных модификаторов. Доказано, что многофункциональное модифицирование улучшает морфологию неметаллических включений, что также способствует повышению уровня механических характеристик. У даній статті розглянуто вплив дії компонентів багатофункціонального модифікатора на формування неметалевих включень у колісній сталі марки КП-Т. Метою даної роботи було дослідження впливу модифікаторів багатофункціональної дії на морфологію і розташування неметалевих включень, а також на стабілізацію і підвищення рівня механічних характеристик. Встановлено, що в даному металі за допомогою введення багатофункціональних модифікаторів у розплав сталі підвищується стабільність хімічного складу й, як наслідок, рівень механічних характеристик. Проведено системні термодинамічні дослідження з можливого впливу компонентів спеціальних модифікаторів при їхній взаємодії з розплавом. Визначено основні термодинамічні параметри з'єднань, які можуть формуватися в розплаві сталей при введенні спеціальних модифікаторів. Доведено, що багатофункціональне модифікування поліпшує морфологію неметалічних включень, що також сприяє підвищенню рівня механічних характеристик.